CLINICAL AND LABORATORY DIAGNOSTICS OF CORONAVIRUS INFECTION - Tursunov Feruz Uktamovich; Turakulov Javlon Sodik ugli; Ibragimova Nadiya Sabirovna; Ergashev Sirojiddin Komiljon ugli (Web of Journals Publishing, 2025)
The relevance of coronavirus infection today remains extremely high and multifaceted. The global pandemic continues to have a significant impact on public health, economic development and social structures. Uneven distribution of vaccines, the emergence of new virus strains and changing public behavior pose additional challenges to health systems.
Keywords: Coronavirus infection, PCR diagnostics, computed tomography, pulse oximetry, complications.